Lithium/yttrium cluster effect on {101-1} twin boundary migration in magnesium - Shuo Wang; Qun Zu (Results in Physics, 2021)
The precipitate with a crystal structure different from the matrix usually plays a great role in the material strength. However, little is known about the contribution of precipitate similar to the matrix structure. Herein, the interaction of {101-1} twin and hexagonal close-packed (HCP) cluster has been investigated by molecular dynamics (MD) simulation and transmission electron microscopy (TEM) observation in magnesium. The sphere-/plate- shaped Li and Y clusters are respectively considered. The MD results show that twinning dislocation (TD) prefers to nucleate in the soft phase and can be pinned at the cluster/matrix interface for Mg-Li alloy and matrix/cluster interface for Mg-Y alloy. The higher stress and larger strain are required to pass through the upper half of Li cluster, signifying a stronger pinning effect in upper region. It is consistent with the experiment results. The twin boundary (TB) can also cut through the hard Y phase under shearing due to its HCP crystal structure and the accumulation of TDs with large Burgers vector. Compared with the different plate-shaped clusters, the strongest mechanical property is expressed on the sample with spherical phase. The finding of HCP-type cluster effect on {101-1} twin boundary migration gives a new insight into the precipitate strengthening mechanism.